Modulation of charge-density waves by superlattice structures - Malvezzi, André Luiz [UNESP]; Paiva, Thereza; dos Santos, Raimundo R. (Amer Physical Soc, 2006)
We discuss the interplay between electronic correlations and an underlying superlattice structure in determining the period of charge density waves (CDW's), by considering a one-dimensional Hubbard model with a repeated (nonrandom) pattern of repulsive (U > 0) and free (U=0) sites. Density matrix renormalization group diagonalization of finite systems (up to 120 sites) is used to calculate the charge-density correlation function and structure factor in the ground state. The modulation period can still be predicted through effective Fermi wave vectors k(F)(*) and densities, and we have found that it is much more sensitive to electron (or hole) doping, both because of the narrow range of densities needed to go from q(*)=0 to pi, but also due to sharp 2k(F)(*)-4k(F)(*) transitions; these features render CDW's more versatile for actual applications in heterostructures than in homogeneous systems.